Susceptibility of Atta sexdens worker ants treated with the immunosuppressant Sandimmun Neoral to Metarhizium anisopliae - Pereira Dornelas, Aline Silvestre; Sarmento, Renato de Almeida; Pedro-Neto, Marçal; da Silva, Daniella Gonçalves; dos Santos, Gil Rodrigues; Nascimento, Mariela Otoni do; Oliveira, Cléia Almeida; Souza, Danival José de (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate if the immunosuppressant Sandimmun Neoral enhances the activity of Metarhizium anisopliae against the leaf-cutting ant Atta sexdens. The vulnerability to the pathogen was measured by comparing the mortality rate of worker ants subjected to the following treatments: immunosuppressant+control, immunosuppressant+M. anisopliae, excipient+control, excipient+M. anisopliae, control+M. anisopliae, and control. Worker ants treated with immunosuppressant+M. anisopliae showed the highest mortality rate in comparison with those subjected to all other treatments. The use of the immunosuppressant together with entomopathogenic fungus controlled leaf-cutting ants in laboratory conditions.